2007
DOI: 10.1136/jcp.2006.044701
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and reliability of oestrogen receptor, progesterone receptor and HER2 in breast carcinoma determined by immunohistochemistry in Australasia: results of the RCPA Quality Assurance Program

Abstract: Background and Aims:Immunohistochemistry (IHC) has replaced radioligand binding assay for the determination of oestrogen receptor (ER) status in breast carcinoma. IHC is also used for assessment of progesterone receptor (PR) and HER2. The Royal College of Pathologists of Australasia (RCPA) Quality Assurance Program (QAP) introduced a breast markers module in 2003 to evaluate the performance of laboratories with IHC for ER, PR and HER2.Methods:An audit of laboratories reporting breast carcinomas was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
(35 reference statements)
4
17
0
2
Order By: Relevance
“…The proportion of breast cancers defined as ER-positive (87.47%) or PR-positive (75.18%) is higher than literaturereported proportions for ER (75%) and PR (55%) [7,14,48,49]. Improved laboratory sensitivity for detecting ER, different quantification techniques, and dichotomous cutoff values for assessing ER and PR account for important interlaboratory variability [36,50,51].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The proportion of breast cancers defined as ER-positive (87.47%) or PR-positive (75.18%) is higher than literaturereported proportions for ER (75%) and PR (55%) [7,14,48,49]. Improved laboratory sensitivity for detecting ER, different quantification techniques, and dichotomous cutoff values for assessing ER and PR account for important interlaboratory variability [36,50,51].…”
Section: Discussionmentioning
confidence: 89%
“…HER-2 as a poor prognostic marker is already now being affected by adjuvant trastuzumab therapy and triple negative tumors may, anyway, eventually become the subgroup with the worst DFI. Also, patients with a triple negative breast cancer suffer from more limited treatment options and exhibit inherent aggressive tumour characteristics as expressed by their high median NPI score [48,49] (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulated ratio of ER and PR expression in breast tumors of Indian women is found to be much lower than that of Western population, where >50% are co-positive for ER and PR (Barnes et al, 1996). Studies from Canada and Australia also reported that 73% and 59% of the BC were ER positive while 58.10% and 61% were PR positive respectively (Rhodes et al, 2000;Francis et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Quality assurance measures are crucial to ensure a sufficient standard of staining quality and accurate interpretation to minimize false positives and negatives, which could lead to inappropriate treatment choices and detrimentally effect patient care. 35 The early studies evaluating ALK fusion immunohistochemistry reported limitations of sensitivity, describing an absence of immunoreactivity in ALK fusion positive NSCLCs. 29,36 In addition, immunohistochemistry can be hindered by poor fixation, variability in staining protocols, limited expertise by pathologists and can be hampered by small biopsies containing minimal tumor cells.…”
Section: Discussionmentioning
confidence: 99%